STRATEGI PENGELOLAAN LANSKAP RUANG TERBUKA BIRU DI DAERAH ALIRAN SUNGAI CILIWUNG - Arkham HS; Hadi Susilo Arifin; RL Kaswanto (http://arl.faperta.ipb.ac.id/, 2014)
The cases occurred in several major cities in the watershed, surface of water bodies, the blue open space (RTB) faced significant disruption. This is caused by changes and reclamation. Consequently, it impacted on water crisis. The objectives of researches: (1) to analyze RTB spatial temporal change in Ciliwung watershed from 1978, 1995, and 2010, (2) to develop strategies management of RTB in Ciliwung watershed. The research used remote sensing methods with the supervised classification. Changes in land cover used Landsat MSS in 1978, Landsat TM 1995 and Landsat ETM + 2010. Strengthen Weaknes Opportunities Threats (SWOT) analysis was used to formulate management strategies in Ciliwung RTB. The results of the spatial analysis showed significant changes when RTB area in 1978-1995 shrinks approximately 27.62 ha (0.07%) and 1995 to 2010 declines approximately 66.01 ha (0.17%). The change directions are dominated by changes RTB into settlements with an area of 114.79 ha (16.96%). RTB management strategies regulations for property developers, the socialization of the important role of RTB, the compliting of RTB infrastructure, and the create a management plan of RTB with the reward and punishment mechanisms for the community.